Objetivos do desenvolvimento sustentável (ODS) no âmbito municipal: análises nos municípios lindeiros ao lago de Itaipu - Silva Junior, José Roberto Martins da (2023)
The objective of the present work is the search to verify, from the master plans, government plans and the multiannual ones, the use of the sustainable development objectives (SDGs), in the public management of the municipalities, especially the neighboring municipalities, about the search for a concept of practical application of sustainability. Such municipalities, affected by the formation of Lake Itaipu, consisting of 16 (sixteen) municipalities, namely: Mundo Novo in the State of Mato Grosso do Sul, Guaíra, Marechal Cândido Rondon, Santa Helena, Missal, Santa Terezinha do Itaipu, São Miguel do Iguaçu, Medianeira, Diamante D'Oeste, Terra Roxa, Foz do Iguaçu, Mercedes, Pato Bragado, Entre Rios do Oeste, São José das Palmeiras and Itaipulândia in the State of Paraná. With the advancement of public policies aimed at sustainable development and the dictates of the 2030 agenda, the aforementioned study will focus on the analysis of municipal public management in order to collect data and information for the discussion about the applications and uses of UN indicators. In order to quantify the indicators, demonstrating, for example, which municipalities have been using them and how they are organizing themselves to make municipal public management more sustainable in accordance with the concept of sustainable development contributed by the United Nations - UN. The research also intends to demonstrate that there is a need for prospects for the future, through projects in the municipalities for full sustainable development, through projects and instruments of governance, environmental education and the relationship between man, nature and the environment, duly balanced so that achieve the objectives proposed by the UN. The research, based on literature and with emphasis on qualitative methods, which seeks to demonstrate the use or not of indicators, and quantitative, tracing comparative parallels between the Lindeiros municipalities.